SOCIAL JUSTICE AND INTERNATIONAL LAW - Peruana de Derecho Internacional, Sociedad (2020)
The transfer of sovereignty of states to be part of the concert of nations is part of theinternational commitment that states have to establish coordination between countries and theconstruction of international law. Social justice is an element that cannot be ignored in the relationsbetween man and the State and have their own weight in modern societies and, now, in internationalrelations. She promotes, as far as possible, social equality and fundamental social values based onthe balanced and harmonious common good.For this reason, it is important to pay attention to social rights, the causes of theirdeterioration and the origin of popular discontent, emphasizing that democracy and respect forhuman rights are indispensable mechanisms for human coexistence.John Rawls and Amartya Sen are two of the philosophers who have marked with theirtheories on social justice an important stage in thought and in the study of its meaning in today'sworld. I present some of the approaches of the Indian philosopher Sen, especially his mostsignificant statements in his work "The idea of Justice". On the other hand, Sen analyzes, from adifferent perspective, Rawls' idea of social justice and criticizes some of the most relevant ideas ofhis work: "Theory of Justice"